2008
DOI: 10.1097/mlg.0b013e3181492400
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Laryngitis: Neuropeptide, Cyclooxygenase, and Cytokine Profile

Abstract: This NGI model results in laryngeal chronic inflammation without direct mechanical aggression of the mucosa and may contribute to the study of future therapeutic approaches to this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…We previously demonstrated that NGI is a good model to study laryngitis in the rat since no direct lesion of the laryngeal epithelium is induced [9]. Additionally, we observed an overexpression of COX-2 enzyme in the laryngeal mucosa [9], which represents the inducible form of the COX enzyme following pathological stimulation in opposition to the constitutive COX-1 isoform [3].…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…We previously demonstrated that NGI is a good model to study laryngitis in the rat since no direct lesion of the laryngeal epithelium is induced [9]. Additionally, we observed an overexpression of COX-2 enzyme in the laryngeal mucosa [9], which represents the inducible form of the COX enzyme following pathological stimulation in opposition to the constitutive COX-1 isoform [3].…”
Section: Introductionmentioning
confidence: 62%
“…Some studies showed a neurogenic component in some pathologies like asthma, rhinitis and rheumatoid arthritis [8]. Recently, we demonstrated a neurogenic factor in a new model of experimental laryngitis [9]. The intraepithelial nerve fibres of the larynx are important for bronchopulmonar defence [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…COX-1 is constitutively expressed. COX-2 gene expression has been demonstrated to increase in response to cytokines, mitogens, and growth factors [7]. High expression of COX-2 in a wide variety of solid epithelial tumors also favors the growth of malignant cells by inhibition of apoptosis and the promotion of angiogenesis [8].…”
Section: Original Studymentioning
confidence: 99%